Examining long run relationship between gold price, inflation and exchange rates for Malaysia: VECM approach - Nordin, Sabariah; Zainuddin, Zaemah; Nordin, Norhafiza; Regupathi, Angappan (Universiti Utara Malaysia, 2012)
This paper is intended to examine the relationship between gold price, inflation and exchange rates.In investment, inflation is always identified as a “mean” that demolishes the value of an asset.In spite of just observing the short run and long run relationships that exist among the underlying variables, this paper is intended to propose an investment alternative which may resolve the negative effect of inflation.To achieve the objectives, this paper employs a cointegration technique of VECM based on three underlying variables of gold price, Malaysian consumer price index (CPI) and exchange rates of RM/US$ for yearly data of 1970 to 2009.The results of the study indicate that there is a cointegration relationship that exists among the three variables.In other words, the three variables are moving towards a long run equilibrium relationship. Both variables, inflation and exchange rates, are found to be the significant determinants of the gold price in the long run.As expected, there is a significant positive relationship that exists between the CPI and the gold price.Results indicate an increase in the CPI by 1 percent will be reflected in an increase in the gold price by 2.5 percent.In other words, this result suggests that holding gold should be considered as a potential hedging strategy to hedge against the inflation.The rise in the gold price will be able to offset the negative effect of the inflation since the value of gold increases more than an increase in the inflation.On the hand, results obtained are not able to show any short run relationship between the variables. Nevertheless, the short run adjustment of the error correction term (ect) is negative as supposed to, even though not significant.In short, results imply that gold is suitable for the long run investment rather than short run, particularly may be because of the huge fluctuations in its price in the short run.